Food-derived dietary alkaloids: structure–biofunctionality relationships in modulating gut microbial biofilms for downregulation of colorectal carcinogenesis - Saikat Mazumder; Debasmita Bhattacharya; Dibyajit Lahiri; Moupriya Nag; Sudhriti Maity; Debpriya Saha; Navin Kumar; Vandana Singh; Shubham Sharma; Shashi Prakash Dwivedi; Mithul Rajeev; Seema Raj; et al. (Food Research International, 2026)

Synergistic microwave enzymatic immersion pretreatment of apple slices: Effects on mass transfer, enzyme activity, and digestive bioaccessibility - Fuxuan Cai; Ganesan Jeevarathinam; Dianbin Su; Huihui Xu; Yanchun Yao; Weiqiao Lv; Sarvesh Rustagi (Food Chemistry, 2026)

Advances in heavy metal removal from fruit juices: implications for food safety and quality control - G. Jeevarathinam; J. Deepa; Amarjit Singh Ningthoujam; Bedanta Rajbongshi; C. Nickhil; Shweta; Snigdha Chetia; Seema Ramniwas; S. Ganga Kishore; Davinder Pal Singh Oberoi; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Critical Reviews in Food Science and Nutrition, 2026)

Microbial-nanobiotechnology for sustainable food preservation, safety, and security: Current challenges and potential solutions - Jibanjyoti Panda; Awdhesh Kumar Mishra; Nishithendu Bikash Nandi; Bishwambhar Mishra; Sarvesh Rustagi; Hrudayanath Thatoi; Pinku Chandra Nath; Yugal Kishore Mohanta (Food and Bioproducts Processing, 2026)

Emerging technologies in watermelon juice Processing: Innovations in preservation and quality enhancement - G. Jeevarathinam; Vismaya K. Sachithanandhan; J. Deepa; V. Arun Prasath; S. Ganga Kishore; Punit Singh; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Food Control, 2026)

Histone modifications in biological age determination: mechanisms, biomarkers, and therapeutic perspectives - Anjali Tripathi; Garima Sharma; Vinay Kumar Pandey; Sarvesh Rustagi; Ashish Ranjan Sharma; Meenakshi Jha; Abhijit Debnath; Jomon George Joy; Jin-Chul Kim; Abhimanyu Kumar Jha (GeroScience, 2026)

Deacidification of vegetable oils: advanced technologies, mechanistic insights, and emerging strategies - G. Jeevarathinam; R. Rahul; J. Deepa; N. Sharath Kumar; C.S. Neethu; G. Sarojini; V. Siva Shankar; Punit Singh; Davinder Pal Singh Oberoi; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Food Chemistry, 2026)

Harnessing light: the role of semiconductor technology in boosting phenolic compounds in fruit and vegetable - Pranav Vashisht; K. Sangeetha; Bharathi Ramesh; Nanje Gowda; Apoorva Prasanna; Raj Singh; R. Nisha; C. Nickhil; Anto Pradeep Raja Charles; Danush Kenchanna; Kaavya Rathnakumar; Chatrapati Veera Raghava Kumar Tamminedi; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Potential health benefits of postbiotics and its utilization as natural food preservatives - Rahul Singh; Poornima Singh; Umme Habiba; Vinay Kumar Pandey; Sawinder Kaur; Sarvesh Rustagi (Food and Humanity, 2025)

Correction: Effect of electromagnetic radiations from mobile towers on genetic damage and genetic polymorphism in humans: a review on India’s perspective - Kanu Priya; Mohini Singh; Lunjapikai Haokip; Shiv Kumar Giri; Anil Kumar; Harjot Singh Gill; Sarvesh Rustagi; Mithul Rajeev; Dibyajit Lahiri; Moupriya Nag (Toxicology and Environmental Health Sciences, 2025)

Effect of electromagnetic radiations from mobile towers on genetic damage and genetic polymorphism in humans: a review on India’s perspective - Kanu Priya; Mohini Singh; Lunjapikai Haokip; Shiv Kumar Giri; Anil Kumar; Harjot Singh Gill; Sarvesh Rustagi; Mithul Rajeev; Dibyajit Lahiri; Moupriya Nag (Toxicology and Environmental Health Sciences, 2025)

A review on microbial-biofilm mediated mechanisms in marine microplastics degradation - Soumyajit Chandra; Dibyajit Lahiri; Moupriya Nag; Debasmita Bhattacharya; Chetan Pandit; Soumya Pandit; Kuldeep Sharma; Mithul Rajeev; Harjot Singh Gill; Sarvesh Rustagi (Antonie van Leeuwenhoek, 2025)

Emergence of potassium solubilizing microbes-assisted crop processing for sustainable food production and microbial complexities - Bhavna Damathia; Diksha Pathania; Ayush Jha; Harsh Sable; Sonu; Pardeep Singh; Vandana Singh; Sarvesh Rustagi; Vishal Chaudhary (Food and Bioproducts Processing, 2025)

Optimizing extraction process of Fish Protein Concentrate from Katley fish (Copper mahseer) using response surface methodology - Hijam Merina Devi; Basant Kumar Singh; Pinku Chandra Nath; Vinay Kumar Pandey; Sarvesh Rustagi; Sajesh Chettri (Bioresource Technology Reports, 2025)

Integrons: the hidden architects of bacterial adaptation, evolution, and the challenges of antimicrobial resistance - Harjeet Singh; Shivani Pandya; Srushti Jasani; Mitesh Patel; Tanvir Kaur; Sarvesh Rustagi; Sheikh Shreaz; Ajar Nath Yadav (Antonie van Leeuwenhoek, 2025)

Application of multivariate analysis and Kohonen Neural Network to discriminate bioactive components and chemical composition of kosovan honey - Hyrije Koraqi; Jolanta Wawrzyniak; Alev Yüksel Aydar; Ravi Pandiselvam; Waseem Khalide; Anka Trajkoska Petkoska; Ioannis Konstantinos Karabagias; Seema Ramniwas; Sarvesh Rustagi (Food Control, 2025)

Antibiotic contamination in wastewater treatment plant effluents: Current research and future perspectives - Parnika Mishra; Gyanendra Tripathi; Vaishnavi Mishra; Talat Ilyas; Irum; Saba Firdaus; Suhail Ahmad; Alvina Farooqui; Neelam Yadav; Sarvesh Rustagi; Sheikh Shreaz; Rajeshwari Negi; et al. (Environmental Nanotechnology, Monitoring & Management, 2025)

Microbes Mediated Nutrient Dynamics for Plant Growth Promotion: Current Research and Future Challenges - Rubee Devi; Tanvir Kaur; Rajeshwari Negi; Babita Sharma; Sanjeev Kumar; Sangram Singh; Ashutosh Kumar Rai; Sarvesh Rustagi; Ashok Yadav; Anu Kumar; Divjot Kour; Ajar Nath Yadav (Indian Journal of Microbiology, 2025)

Concentration-dependent functional impact of high molecular weight (HMW) and low molecular weight (LMW) glutenins on dough rheology and instant noodle quality in distinct wheat varieties - Aastha Dewan; Nisha Chaudhary; Priya Dangi Malik; Manisha Malik; Narpindar Singh; B.S. Khatkar; Sarvesh Rustagi; R. Pandiselvam (Journal of Cereal Science, 2025)

Radical species generating technologies for decontamination of Listeria species in food: a recent review report - Rathnakumar Kaavya; Bharathipriya Rajasekaran; Kartik Shah; C. Nickhil; Suguna Palanisamy; Suriya Palamae; Anandu Chandra Khanashyam; R. Pandiselvam; Soottawat Benjakul; Priyamavada Thorakattu; Bharathi Ramesh; Fawzan Sigma Aurum; et al. (Critical Reviews in Food Science and Nutrition, 2025)

In silico analysis of Phlogacanthus thyrsiflorus Nees. and its protective effects against cardiomyopathic stress induced by alloxan in mice model - Jutishna Bora; Sumira Malik; Smita Lata; Taranga Jyoti Baruah; Sarvesh Rustagi; Himanshu Ranjan; Ravi K. Deshwal; Seema Ramniwas; Nayan Talukdar (Vegetos, 2025)

Macronutrients-availing microbiomes: biodiversity, mechanisms, and biotechnological applications for agricultural sustainability - Tanvir Kaur; Rubee Devi; Rajeshwari Negi; Harpreet Kour; Sangram Singh; Sofia Sharief Khan; Chandresh Kumari; Divjot Kour; Sohini Chowdhury; Monit Kapoor; Ashutosh Kumar Rai; Sarvesh Rustagi; et al. (Folia Microbiologica, 2025)

Recent advances on artificial intelligence-based approaches for food adulteration and fraud detection in the food industry: Challenges and opportunities - Puja Das; Ammar B. Altemimi; Pinku Chandra Nath; Mehak Katyal; Radha krishnan Kesavan; Sarvesh Rustagi; Jibanjyoti Panda; Satya Kumar Avula; Prakash Kumar Nayak; Yugal Kishore Mohanta (Food Chemistry, 2025)

Unveiling the effects of ZnO nanoparticle incorporated chitosan coating on postharvest quality of eggplant (Solanum melongena L.) - Kanika Dulta; Gözde Koşarsoy Ağçeli; Somvir Singh; Vinay Kumar Pandey; Arti Thakur; P.K. Chauhan; Junaid Aman; Sarvesh Rustagi (Food Control, 2025)

Recent insights on microfluidics applications for food quality and safety analysis: A comprehensive review - Shivangi Srivastava; Vinay Kumar Pandey; Anurag Singh; Kshirod Kumar Dash; Aamir Hussain Dar; Sarvesh Rustagi (Food Control, 2025)

Azolla for agro-environmental sustainability - Divjot Kour; Seema Ramniwas; Sanjeev Kumar; Ashutosh Kumar Rai; Sangram Singh; Sarvesh Rustagi; Ajar Nath Yadav; Amrik Singh Ahluwalia (Vegetos, 2024)

Green chemistry revolutionizing sustainability in the food industry: A comprehensive review and call to action - Arun Kumar Gupta; Tridip Boruah; Payel Ghosh; Ali Ikram; Sandeep Singh Rana; Anjaly Shanker M; Archana Bachetti; Avinash Kumar Jha; Bindu Naik; Vijay Kumar; Sarvesh Rustagi (Sustainable Chemistry and Pharmacy, 2024)

Essential oil-nanoemulsion based edible coating: Innovative sustainable preservation method for fresh/fresh-cut fruits and vegetables - Ramesh Sharma; Pinku Chandra Nath; Puja Das; Sarvesh Rustagi; Minaxi Sharma; Natarajan Sridhar; Tridip Kumar Hazarika; Priya Rana; Prakash Kumar Nayak; Kandi Sridhar (Food Chemistry, 2024)

Enforcing the antioxidant properties of blackberries against breast cancer by activating different cell signaling mechanisms: An updated review - Anjali Tripathi; Vinay Kumar Pandey; Hridyanshi Mishra; Aamir Hussain Dar; Gurmeet Singh; Sarvesh Rustagi; Ghassan Sulaiman; Abhimanyu Kumar Jha (Food Bioscience, 2024)

Transforming waste into valuable resources: Harnessing the potential of pectin obtained from organic waste for the food and healthcare industries - Nishesh Sharma; Punit Arora; Priyvart Choudhary; Vinay Kumar Pandey; Aamir Hussain Dar; Sarvesh Rustagi; Harish Chandra Joshi (Food Bioscience, 2024)

Exploring the potential of metallic and metal oxide nanoparticles for reinforced disease management in agricultural systems: A comprehensive review - Adnan Raza; Krisha Khandelwal; Soumya Pandit; Mohini Singh; Sandeep Kumar; Sarvesh Rustagi; Nishant Ranjan; Rajan Verma; Kanu Priya; Ram Prasad (Environmental Nanotechnology, Monitoring & Management, 2024)

Innovative approaches to pectin processing: Enhancing techno-functional properties for applications in food and beyond - Gurjeet Kaur; Zakir Showat Khan; Ömer Said Toker; Mohmad Sayeed Bhat; Bulent Basyigit; Abdullah Kurt; Sarvesh Rustagi; Shweta Suri; Samaneh Hatami; Shemilah Fayaz; Thameed Aijaz (Bioactive Carbohydrates and Dietary Fibre, 2024)

Potential effect of novel endophytic nitrogen fixing diverse species of Rahnella on growth promotion of wheat (Triticum aestivum L.) - Kusam Lata Rana; Rajeshwari Negi; Babita Sharma; Ashok Yadav; Rubee Devi; Tanvir Kaur; Sheikh Shreaz; Sarvesh Rustagi; Ashutosh Kumar Rai; Sangram Singh; Divjot Kour; Ajar Nath Yadav (Journal of Crop Science and Biotechnology, 2024)

Microbial consortium with multifunctional attributes for the plant growth of eggplant (Solanum melongena L.) - Tanvir Kaur; Rubee Devi; Rajeshwari Negi; Sanjeev Kumar; Sangram Singh; Sarvesh Rustagi; Sheikh Shreaz; Ashutosh Kumar Rai; Divjot Kour; Ajar Nath Yadav (Folia Microbiologica, 2024)

Microbial consortia mediated regulation of plant defense: A promising tool for sustaining crops protection - Rajeshwari Negi; Babita Sharma; Faezeh Parastesh; Simranjeet Kaur; Sofia Sharief Khan; Divjot Kour; Sangram Singh; Ashutosh Kumar Rai; Sarvesh Rustagi; Neelam Yadav; Sheikh Shreaz; Tareq A. Madouh; et al. (Physiological and Molecular Plant Pathology, 2024)

Carbon dots-nanosensors: Advancement in food traceability for a sustainable environmental development - Zaryab Shafi; Vinay Kumar Pandey; Rahul Singh; Sarvesh Rustagi (Food Control, 2024)

Encapsulation of debittered pomelo juice using novel Moringa oleifera exudate for enrichment of yoghurt: A techno-functional approach - Arun Kumar Gupta; Tanuva Das; Avinash Kumar Jha; Bindu Naik; Vijay Kumar; Sarvesh Rustagi; Javed Masood Khan (Food Chemistry, 2024)

Slaughterhouse blood: A state-of-the-art review on transforming by-products into valuable nutritional resources and the role of circular economy - Arun Kumar Gupta; Nurrulhidayah Ahmad Fadzlillah; Siti Jamilah Mohd Sukri; Opeyemi Adewumi Adediran; Muzamil Ahmad Rather; Bindu Naik; Vijay Kumar; Alaa El-Din Ahmed Bekhit; Mohd Anuar Ramli; Avinash Kumar Jha; Panchi Rani Neog; Shuvam Bhuyan; et al. (Food Bioscience, 2024)

Adsorption parameters optimization of spent coffee ground biochar for methylene blue removal using response surface methodology - Thachnatharen Nagarajan; Nazifa Huda Binti Mohd Fekeri; Gunasunderi Raju; Subramani Shanmugan; Gautham Jeppu; Rashmi Walvekar; Sarvesh Rustagi; Mohammad Khalid (Chemosphere, 2024)

Essential oils and their critical implications in human use - Pinku Chandra Nath; Pritam Dey; Tania Paul; Saurav Shil; Sambit Sarkar; Sarvesh Rustagi; Debasmita Bhattacharya; Kunal Vora; Rupak Roy (Biocatalysis and Agricultural Biotechnology, 2024)

Bacterial biofilms: Pathogenesis, monitoring, treatment approaches and associated challenges - Sunny Dhiman; Anu Kumar; Gagandeep Kaur; Gunjan Mukherjee; Sarvesh Rustagi; Sheikh Shreaz; Rajeshwari Negi; Ajar Nath Yadav (Biologia, 2024)

Microbial Consortia: Promising Tool as Plant Bioinoculants for Agricultural Sustainability - Rajeshwari Negi; Babita Sharma; Tawseefa Jan; Tanvir Kaur; Sohini Chowdhury; Monit Kapoor; Sangram Singh; Anu Kumar; Ashutosh Kumar Rai; Sarvesh Rustagi; Sheikh Shreaz; Divjot Kour; et al. (Current Microbiology, 2024)

Macromolecular, thermal, and nonthermal technologies for reduction of glycemic index in food-A review - G. Jeevarathinam; Seema Ramniwas; Punit Singh; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq; R. Pandiselvam (Food Chemistry, 2024)

Nano-biogenic heavy metals adsorptive remediation for enhanced soil health and sustainable agricultural production - Ayush Jha; Bindiya Barsola; Diksha Pathania; Sonu; Pankaj Raizada; Pankaj Thakur; Pardeep Singh; Sarvesh Rustagi; Ajit Khosla; Vishal Chaudhary (Environmental Research, 2024)

In-silico analysis of antiviral fungal inhibitors against Mpro receptor protein - Arpita Roy; Nikita Sharma; Ritika Luthra; Saanya Yadav; Shreeja Datta; Aaryan Gupta; Vaseem Raja; Sarvesh Rustagi; Sumira Malik (Vegetos, 2024)

Re-emergence of Nipah virus outbreak in Kerala, India: a global health concern - Prakasini Satapathy; Mahalaqua Nazli Khatib; Shilpa Gaidhane; Quazi Syed Zahiruddin; Sarvesh Rustagi; Neelima Kukreti; Rachana Mehta; Ranjit Sah (Infectious Diseases, 2024)

Investigating the adsorption potential of char derived from waste latex for methylene blue removal - Thachnatharen Nagarajan; Khirthiga Vilosamy; Gunasunderi Raju; Subramani Shanmugan; Rashmi Walvekar; Sarvesh Rustagi; Mohammad Khalid (Chemosphere, 2024)

Sustainable solutions for food security: Evaluating pre-treatment technologies in the growing fruits and vegetables industry of India - Aroma Joshi; Arun Kumar Gupta; Mansi; Shivani Semwal; Nandini Deoli; Muzamil Ahmad Rather; Bindu Naik; Vijay Kumar; Avinash Kumar Jha; Sarvesh Rustagi; Manpreet Singh Preet (Sustainable Chemistry and Pharmacy, 2024)

Utilizing marine algal metabolites to fight neurodegenerative diseases - Bindu Naik; Shruti Richa; Shivangi Bharadwaj; Sadhna Mishra; Vijay Kumar; Vivek Kumar; Per Erik Joakim Saris; Arun Kumar Gupta; Ritesh Mishra; Uttam Gupta; Sarvesh Rustagi; Manpreet Singh Preet (Frontiers in Marine Science, 2024)
Marine algae are thought to be a source of various metabolites that have a wide range of positive effects on human health. The pharmacological properties of algal metabolites, including their antioxidant, anti-inflammatory, cholesterol homeostasis, protein clearance, and anti-amyloidergic effects, lend credence to their protective efficacy against oxidative stress, neuroinflammation, mitochondrial dysfunction, and impaired proteostasis, all of which are involved in the pathophysiology of neurodegenerative disorders. There are currently no clinical trials on the effects of marine algae on neuroinflammation; however, considering the significant biological activities that have been established by in vitro and animal research, we expect that there will be clinical trials on this topic in the not-too-distant future. The most recent and important findings on the potentially neuroprotective effects of the anti-inflammatory properties of marine algae were chosen for this study. Next, we conducted a literature review on the neuroprotective potential of algal compounds, along with the underlying pharmacological mechanism, and finally, we evaluated recent advances in therapeutics.

Correction: A systematic review of potential bioactive compounds from Saccharomyces cerevisiae: exploring their applications in health promotion and food development - Balaji Doolam; Bishwambhar Mishra; Divyamshu Surabhi; Sanjeeb Kumar Mandal; Spoorthi Sada; Naru Rakesh Reddy; Jibanjyoti Panda; Sarvesh Rustagi; Awdhesh Kumar Mishra; Yugal Kishore Mohanta (Environment, Development and Sustainability, 2024)

Synergistic effect of minerals solubilizing and siderophores producing bacteria as different microbial consortium for growth and nutrient uptake of oats (Avena sativa L.) - Rubee Devi; Marwa Fadhil Alsaffar; Duraid K.A. AL-Taey; Sanjeev Kumar; Rajeshwari Negi; Babita Sharma; Tanvir Kaur; Sarvesh Rustagi; Divjot Kour; Ajar Nath Yadav; Amrik Singh Ahluwalia (Vegetos, 2024)

Association of air pollution with risk and severity of obstructive sleep apnea: A systematic review and meta-analysis - Tahani Alrahbeni; Jeetendra Kumar Gupta; Anas Alkhouri; Ladi Alik Kumar; Ahmed Mahal; Khalid Al-Mugheed; Prakasini Satapathy; Neelima Kukreti; Mahalaqua Nazli Khatib; Shilpa Gaidhane; Abhay M. Gaidhane; Sarvesh Rustagi; et al. (NeuroToxicology, 2024)

Bamboo stem derived biochar for biosorption of Cadmium (II) ions from contaminated wastewater - Harsh Sable; Vaishali Kumar; Richa Mishra; Vandana Singh; Arpita Roy; Ashutosh Kumar Rai; Nishant Ranjan; Sarvesh Rustagi; Soumya Pandit (Environmental Nanotechnology, Monitoring & Management, 2024)

A systematic review of potential bioactive compounds from Saccharomyces cerevisiae: exploring their applications in health promotion and food development - Balaji Doolam; Bishwambhar Mishra; Divyamshu Surabhi; Sanjeeb Kumar Mandal; Spoorthi Sada; Naru Rakesh Reddy; Jibanjyoti Panda; Sarvesh Rustagi; Awdhesh Kumar Mishra; Yugal Kishore Mohanta (Environment, Development and Sustainability, 2024)

Effect of indigenous mineral availing microbial consortia and cattle manure combination for growth of maize (Zea mays L.) - Rubee Devi; Marwa Fadhil Alsaffar; Duraid K.A. AL-Taey; Sanjeev Kumar; Rajeshwari Negi; Babita Sharma; Sangram Singh; Ashutosh Kumar Rai; Sarvesh Rustagi; Ashok Yadav; Tanvir Kaur; Divjot Kour; et al. (Vegetos, 2024)

Isolation and characterization of endophytic bacteria from medicinal plants (Berberis aristata and Xanthium strumarium) for Rosemary plant growth promotion - Babita Sharma; Rajeshwari Negi; Harpreet Kour; Seema Ramniwas; Sanjeev Kumar; Sarvesh Rustagi; Sangram Singh; Divjot Kour; Ajar Nath Yadav; Amrik Singh Ahluwalia (Vegetos, 2024)

Degradation of food dyes via biological methods: A state-of-the-art review - Vandana Singh; Chetan Pandit; Arpita Roy; Soumya Pandit; Ashutosh Kumar Rai; Anju Rani; Nishant Ranjan; Sarvesh Rustagi; Sumira Malik (Bioresource Technology Reports, 2024)

Valorization of dairy wastes into wonder products by the novel use of microbial cell factories - Vandana Chaudhary; Priyanka Kajla; Digvijay Verma; Tejinder Pal Singh; Anjineyulu Kothakota; V. Arun Prasath; G. Jeevarathinam; Manoj Kumar; Seema Ramniwas; Sarvesh Rustagi; R. Pandiselvam (Trends in Food Science & Technology, 2023)

A critical review on therapeutic approaches of CRISPR-Cas9 in diabetes mellitus - Jutishna Bora; Ankita Dey; Antonia R. Lyngdoh; Archna Dhasmana; Anuj Ranjan; Shristi Kishore; Sarvesh Rustagi; Hardeep Singh Tuli; Abhishek Chauhan; Prangya Rath; Sumira Malik (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Cancer treatment and toxicity outlook of nanoparticles - Neetika; Mamta Sharma; Pankaj Thakur; Paras Gaur; Gokana Mohana Rani; Sarvesh Rustagi; Rishi Kumar Talreja; Vishal Chaudhary (Environmental Research, 2023)

Analysing role of airborne particulate matter in abetting SARS-CoV-2 outbreak for scheming regional pandemic regulatory modalities - Pradeep Bhadola; Vishal Chaudhary; Kalaimani Markandan; Rishi Kumar Talreja; Sumit Aggarwal; Kuldeep Nigam; Mohammad Tahir; Ajeet Kaushik; Sarvesh Rustagi; Mohammad Khalid (Environmental Research, 2023)

A review on therapeutic mechanism of medicinal plants against osteoporosis: effects of phytoconstituents - Shilpa Kumari; Mohini Singh; Nupur; Smita Jain; Neha Verma; Sumira Malik; Sarvesh Rustagi; Kanu Priya (Molecular Biology Reports, 2023)

Panorama of biogenic nano-fertilizers: A road to sustainable agriculture - Ayush Jha; Diksha Pathania; Sonu; Bhavna Damathia; Pankaj Raizada; Sarvesh Rustagi; Pardeep Singh; Gokana Mohana Rani; Vishal Chaudhary (Environmental Research, 2023)

Diversity, distribution and role of probiotics for human health: Current research and future challenges - Tawseefa Jan; Rajeshwari Negi; Babita Sharma; Divjot Kour; Sanjeev Kumar; Ashutosh Kumar Rai; Sarvesh Rustagi; Sangram Singh; Mohd Aaqib Sheikh; Krishan Kumar; Naseer Ahmed; Ajar Nath Yadav (Biocatalysis and Agricultural Biotechnology, 2023)

Implications of cold plasma and plasma activated water on food texture- a review - M. Anjaly Shanker; Anandu Chandra Khanashyam; R. Pandiselvam; T. Jayasree Joshi; Pinchu Elizabath Thomas; Yue Zhang; Sarvesh Rustagi; Sweety Bharti; Rohit Thirumdas; Manoj Kumar; Anjineyulu Kothakota (Food Control, 2023)

Substantial utilization of food wastes for existence of nanocomposite polymers in sustainable development: a review - Anjali Tripathi; Shivangi Srivastava; Vinay Kumar Pandey; Rahul Singh; Parmjit S. Panesar; Aamir Hussain Dar; Sarvesh Rustagi; Rafeeya Shams; R. Pandiselvam (Environment, Development and Sustainability, 2023)

Bio-derived smart nanostructures for efficient biosensors - Vishal Chaudhary; Sarvesh Rustagi; Ajeet Kaushik (Current Opinion in Green and Sustainable Chemistry, 2023)

Next-generation nanophotonic-enabled biosensors for intelligent diagnosis of SARS-CoV-2 variants - Bakr Ahmed Taha; Yousif Al Mashhadany; Qussay Al-Jubouri; Affa Rozana Bt Abdul Rashid; Yunhan Luo; Zhe Chen; Sarvesh Rustagi; Vishal Chaudhary; Norhana Arsad (Science of The Total Environment, 2023)

Biogenic green metal nano systems as efficient anti-cancer agents - Vishal Chaudhary; Sonu; Ruchita Chowdhury; Prachi Thukral; Diksha Pathania; Shivani Saklani; Lucky; Sarvesh Rustagi; Akash Gautam; Yogendra Kumar Mishra; Pardeep Singh; Ajeet Kaushik (Environmental Research, 2023)

Agro-waste to sustainable energy: A green strategy of converting agricultural waste to nano-enabled energy applications - Sonu; Gokana Mohana Rani; Diksha Pathania; Abhimanyu; Reddicherla Umapathi; Sarvesh Rustagi; Yun Suk Huh; Vijai Kumar Gupta; Ajeet Kaushik; Vishal Chaudhary (Science of The Total Environment, 2023)